2007
DOI: 10.1007/s00421-007-0446-3
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training improves post-exercise cardiac autonomic modulation in obese women with and without type 2 diabetes

Abstract: Obesity and type 2 diabetes (T2D) are associated with abnormal cardiovascular autonomic function and increased risk for cardiac complications, especially after exercise. Since improvements at rest are not always observed after training, we investigated changes in resting and post-exercise autonomic function in obese women with and without T2D after16-week of walking training. Heart rate (HR) variability (HRV) and baroreflex sensitivity (BRS) were measured at rest and 20 min after a 20 min bout of treadmill exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
2
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 49 publications
8
85
2
7
Order By: Relevance
“…41,42 Cross-sectional data showed that endurancetrained participants exhibit a more rapid HR recovery than their untrained counterparts after exercise at similar relative work loads. 43,44 Concordant to some intervention studies, 13,45,19 but at variance with others, 17,18 we found HR recovery to be significantly faster after HI training, and to a lesser extent, also after LI training. Training did not affect post-exercise HRV, which is compatible with the observations of Perini et al, 18 MĂ€rtinmaki et al 17 and Verheyden et al, 19 who also did not find any change in post-exercise HRV after, respectively, 8 weeks, 14 weeks and 1 year of low to high-intensity endurance training.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…41,42 Cross-sectional data showed that endurancetrained participants exhibit a more rapid HR recovery than their untrained counterparts after exercise at similar relative work loads. 43,44 Concordant to some intervention studies, 13,45,19 but at variance with others, 17,18 we found HR recovery to be significantly faster after HI training, and to a lesser extent, also after LI training. Training did not affect post-exercise HRV, which is compatible with the observations of Perini et al, 18 MĂ€rtinmaki et al 17 and Verheyden et al, 19 who also did not find any change in post-exercise HRV after, respectively, 8 weeks, 14 weeks and 1 year of low to high-intensity endurance training.…”
Section: Discussionsupporting
confidence: 89%
“…11 Further, regular physical activity has been shown to lower resting HR; 12 to improve HR recovery after acute exercise 12,13 and to increase global HRV [14][15][16] in several studies, though not all. 15,[17][18][19] These equivocal results could be because of differences in training characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are confirmed by that of Jurca et al in 2004 who, after 8 weeks of moderate exercise training in females, showed improved vagal modulation of heart rate on 10-min resting ECGs [36]. Many previous studies done on diseased populations to evaluate the effect of short-term exercise intervention on short-term HRV modification assessed only supine variables [37][38][39][40][41][42][43]. Sandercock et al in 2007 observed significant increases in the supine RR interval, SDRR, LF(ln) and HF In the present study, only the RR interval increased significantly in the supine position, while the other variables did not show significant changes in favour of the exercise group.…”
Section: Discussionsupporting
confidence: 89%
“…Similar studies, e.g. on diabetic [43,45] and cardiac patients [38,40,41], had equal or even less participants. Heart rate variability was the only tool used to assess the function of the autonomic nervous system.…”
Section: Discussionmentioning
confidence: 85%
“…Notably, in heart failure and after myocardial infarction, interventions like physical training have generated rather strong evidence of a reversal of autonomic abnormalities [24,25]. Recent studies also seem to confirm that autonomic abnormalities can also be favourably influenced by physical exercise in patients with type 2 diabetes [47,48]. On the other hand, our findings are not in contrast with the development of progressive autonomic neuropathy at a later stage.…”
Section: Discussionsupporting
confidence: 69%